Structural development of Ijarah Sukuk: an appraisal - Adam Sa'ad, Auwal (IIUM Press, 2019)
Sukuk structures rely on the performance of an underlying asset or on a contractual arrangement pertaining to that specific asset. This makes sukuk an important facility in Islamic finance since it can be used to provide regular payments throughout the life of the financing plan. This study highlights some important sukuk structures, such as ijarah for asset acquisition and sukuk with a sale and lease-backed structure. Additionally, this study suggests some important proposals to help overcome the Shari’ah issues in sukuk structures. This study suggests that sukuk structures involving the combination of sale and lease-backed contracts should involve a third party who enters into the Ijarah transaction with the investors rather than the originator himself. A benefit of this change will help avoid Inah Ijariyyah (Inah trick for) in the structure. The sukuk structure for asset securitization on the other hand, should not be traded in the secondary market because it involves a sale of debt for debt which is prohibited according to the Shari’ah principles. As for the forward lease sukuk, sukuk holders should wait for the commencement of the project before trading their sukuk in the secondary markets. This is to ensure that the Ijarah property exists before the sale process began.